Grupos de insetos visitantes florais da lichieira (Litchi chinensis Sonn.) em Jaboticabal, Estado de São Paulo, Brasil - Martins, Ivan Carlos Fernandes; De Lima Cavallari, Ludmilla [UNESP]; Haddad, Gianni Queiroz [UNESP]; Augusto, Tiago [UNESP]; Cividanes, Francisco Jorge [UNESP]; Martins, Antonio Baldo Geraldo [UNESP] (My University, 2013)
The objective of this study was to identify the groups of insects that are found visiting flowers of litchi, to determine the time of the visits, to analyze the influence of the inflorescence height in the occurrence of floral visitors and to verify if the incidence of sunlight benefits the visits. The experiment was corried in Faculdade de Ciências Agrárias e Veterinárias da Universidade Estadual Paulista, FCAV/UNESP. The observations were made in August and September 2008, totaling five observations in the whole period. Two observation periods were established for each day: 10:00am to 12:00am and 4:00pm to 6:00pm, and we observed four points within the orchard. The data of floral visitors noted to different hours, heights and sunlight were subjected to analysis of variance and the means were compared by Tukey 5%. Six orders of insects were observed: Hymenoptera, Diptera, Hemiptera, Coleoptera, Lepidoptera and Neuroptera. The time from 10:00 to 12:00 was the most favorable for observation of insect visitors. There were differences in the heights observations from 0.0 to 0.5 and 1.6 to 2.0 meters. There was also a difference in the observations of insects visiting the flowers of litchi when they faced the sun or were shaded.
Groups of floral visitors insects of the litchi (Litchi chinensis Sonn.) in Jaboticabal, São Paulo State, Brazil.
Keywords: Hymenoptera; Inflorescence; Litchi chinensis; Pollinator